2022
DOI: 10.1158/2326-6066.cir-21-0806
|View full text |Cite
|
Sign up to set email alerts
|

CDK2 Inhibition Enhances Antitumor Immunity by Increasing IFN Response to Endogenous Retroviruses

Abstract: Inhibitors of cyclin-dependent kinase-2 (CDK2) are commonly used against several solid tumors, and their primary mechanisms of action were thought to include cell proliferation arrest, induction of cancer cell apoptosis and induction of differentiation. Here, we found that CDK2 inhibition by either small molecular inhibitors or genetic Cdk2 deficiency promoted antitumor immunity in murine models of fibrosarcoma and lung carcinoma. Mechanistically, CDK2 inhibition reduced phosphorylation of RB protein and trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Of most interest to us because of potential novelty for treating phenotypic plastic PCa was the cell cycle related cyclin-dependents kinases (CDK) which included CDK2, CDK5, and CDK7. Based on information gained from this analysis and the success of CDK inhibitors in other cancers (49,50), we applied the DEMETER computational method (44) to infer the dependency of these three CDK genes in the human PCa cell lines mentioned in figure 3. We found that CDK2 demonstrated consistent dependency within all PCa cell lines including the H660 cell line ( Figure 5C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of most interest to us because of potential novelty for treating phenotypic plastic PCa was the cell cycle related cyclin-dependents kinases (CDK) which included CDK2, CDK5, and CDK7. Based on information gained from this analysis and the success of CDK inhibitors in other cancers (49,50), we applied the DEMETER computational method (44) to infer the dependency of these three CDK genes in the human PCa cell lines mentioned in figure 3. We found that CDK2 demonstrated consistent dependency within all PCa cell lines including the H660 cell line ( Figure 5C ).…”
Section: Resultsmentioning
confidence: 99%
“…Tissue sections were imaged using an BZ-X810 microscope (Keyence). Images were de-identified and 5 random fields per section were run through QuPath image analysis software (49) to quantify positive DAB-stained cells (as a percentage of total cells).…”
Section: Immunohistochemical Staining's and Quantification Of Subcuta...mentioning
confidence: 99%
“…across 33 different tumors confirmed the involvement of CDK2 in activating immune response, cell adhesion, migration, and the PI3K‐AKT signaling pathway. The study by Chen et al 21 . found that inhibiting CDK2 promotes antitumor immunity in fibrosarcoma and lung cancer mouse models.…”
Section: Introductionmentioning
confidence: 99%
“…Fadraciclib, a highly selective inhibitor targeting CDK2, has shown antitumor effects in TNBC based on studies by Frame et al 19 The research by Liu et al 20 across 33 different tumors confirmed the involvement of CDK2 in activating immune response, cell adhesion, migration, and the PI3K-AKT signaling pathway. The study by Chen et al 21 found that inhibiting CDK2 promotes antitumor immunity in fibrosarcoma and lung cancer mouse models.…”
Section: Introductionmentioning
confidence: 99%
“…The transcription of multiple proinflammatory genes is upregulated in a CDK-dependent fashion throughout the G1 phase 5 . In the context of antitumor immunity in fibrosarcoma and lung carcinoma, inhibiting CDK2 leads to the RB protein being phosphorylated, which results in increased production of type I IFN 6 . Another study demonstrated that inhibiting CDKs or the knockdown of CDKs activities caused a significant blockade in IFN release from culture supernatants 7 .…”
Section: Introductionmentioning
confidence: 99%